Analyzing Illegal Trade On The Dark Web - Zaid Mundher (Universitas Khairun, 2025)
Internet can be divided, in terms of accessibility, into three main categories: Surface web, Deep web, and Dark web. The dark part is considered the most dangerous of these types due to the difficulty of tracking its users and the anonymity it offers, making it widely used for illegal activities. This research aims to measure the prevalence of illegal activities in Iraq and some neighboring countries, specifically Syria, Saudi Arabia, and Iran. The activities tracked include: drug trafficking, fake documents, and weapons trafficking. The search engine